Peptidoglycan synthesis in L-phase variants of Bacillus licheniformis and Bacillus subtilis. - Ward, J B (1975)
Stable L-phase variants isolated from Bacillus licheniformis and Bacillus subtilis, when grown in osmotically stabilized media, do not synthesize peptidoglycan but have been found to accumulate the nucleotide precursors of this polymer. The enzymes involved in the synthesis of these precursors and the later membrane-bound stages of peptidoglycan synthesis have been investigated, and the L-phase variants have been shown to contain lesions, which provide a rational explanation for the absence of peptidoglycan and for the nature of the precursor accumulated. The majority of the L-phase variants contained a single enzymic defect, but two strains were isolated with double lesions. Five out of seven strains examined accumulated uridine 5'-diphosphate (UDP)-MurAc-L-ala-D-glu and were unable to synthesize diaminopimelic acid as a consequence of a defect in aspartate-beta-semialdehyde dehydrogenase activity. Two strains were deficient in UDP-MurAc: L-alanine ligase and accumulated UDP-MurAc. One strain accumulated the complete nucleotide precursor UDP-MurAc-L-ala-D-glu-mA2pm-D-ala-D-ala and was deficient in phospho-N-acetylmuramyl pentapeptide translocase. A second strain also had this lesion, together with defective aspartate-beta-semialdehyde dehydrogenase activity. The other enzymes of peptidoglycan synthesis were present in the L-phase variants, with activities similar to those found in the parent bacilli grown under identical conditions. Membrane preparations from certain of the L-phase variants were also capable of synthesizing the secondary polymers poly(glycerol phosphate) teichoic acid and teichuronic acid and also a polymer of N-acetylglucosamine.